2012
DOI: 10.1371/journal.pone.0041587
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clonal Distribution of pcpA, psrP and Pilus-1 among Pediatric Isolates of Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is the leading cause of vaccine-preventable deaths globally. The objective of this study was to determine the distribution and clonal type variability of three potential vaccine antigens: Pneumococcal serine-rich repeat protein (PsrP), Pilus-1, and Pneumococcal choline binding protein A (PcpA) among pneumococcal isolates from children with invasive pneumococcal disease and healthy nasopharyngeal carriers. We studied by Real-Time PCR a total of 458 invasive pneumococcal isolates and 89 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 42 publications
7
32
1
Order By: Relevance
“…A monovalent PhtD vaccine was shown to be well tolerated and immunogenic in a phase I trial, 19 and we have confirmed that the antibodies induced by the vaccine are functional in a mouse passive protection sepsis model 20 . Likewise, immunization with PcpA, another highly conserved surface protein, 21,22 has been shown to be protective in active immunization murine models of both sepsis and pneumonia 22 . Furthermore, expression of PcpA is increased in environments low in Mn 2+ , including serum and other internal sites 22,23 …”
Section: Introductionsupporting
confidence: 61%
“…A monovalent PhtD vaccine was shown to be well tolerated and immunogenic in a phase I trial, 19 and we have confirmed that the antibodies induced by the vaccine are functional in a mouse passive protection sepsis model 20 . Likewise, immunization with PcpA, another highly conserved surface protein, 21,22 has been shown to be protective in active immunization murine models of both sepsis and pneumonia 22 . Furthermore, expression of PcpA is increased in environments low in Mn 2+ , including serum and other internal sites 22,23 …”
Section: Introductionsupporting
confidence: 61%
“…Serotypes with a high attack rate are bad colonizers, and different studies have shown that they have important virulence factors associated with the production of pleuropneumonia or other clinical manifestations of IPD [22]. Moreover, the frequency of low-MBL genotypes was observed to be especially high (46.2%) in younger children with IPD caused by opportunistic serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies show that serotype 35B is capable of forming substantial amounts of biofilm, similar to 19F and 19A, which may facilitate nasopharyngeal colonization and mucosal disease (35). Pneumococcal virulence factors such as pili have been found among CC558 and CC156 isolates (25,36,37). These virulence factors facilitate colonization, and they are thought to contribute to invasiveness as well (38).…”
Section: Fig 4 Eburst Analysis Of Penicillin Mic Distribution and Mulmentioning
confidence: 99%